2000
DOI: 10.1016/s1074-7613(00)00055-8
|View full text |Cite
|
Sign up to set email alerts
|

Tyk2 Plays a Restricted Role in IFNα Signaling, Although It Is Required for IL-12-Mediated T Cell Function

Abstract: Janus kinases (Jaks) play an important role in signal transduction via cytokine receptors. Tyk2 is a Janus kinase, and we developed tyk2-deficient mice to study the requirement for tyk2 in vivo. Tyk2-deficient mice show no overt developmental abnormalities; however, they display a lack of responsiveness to a small amount of IFNalpha, although a high concentration of IFNalpha can fully transduce its signal even in the absence of tyk2. Furthermore, IL-12-induced T cell function is defective in these mice. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
287
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 305 publications
(314 citation statements)
references
References 30 publications
24
287
2
1
Order By: Relevance
“…The response to other cytokines that in the past were thought to signal via Tyk2 kinase (e.g. IL-3, IL-6, IL-10 and G-CSF) was unaltered in Tyk2 -/-cells [17,18]. The LPSinduced expression of iNOS in macrophages was completely dependent on Tyk2 [17].…”
Section: Figmentioning
confidence: 93%
See 2 more Smart Citations
“…The response to other cytokines that in the past were thought to signal via Tyk2 kinase (e.g. IL-3, IL-6, IL-10 and G-CSF) was unaltered in Tyk2 -/-cells [17,18]. The LPSinduced expression of iNOS in macrophages was completely dependent on Tyk2 [17].…”
Section: Figmentioning
confidence: 93%
“…In an earlier study Shimoda et al [18] concluded that Tyk2 is indispensable for the IL-12 response of unseparated CD3 + spleen cells as well as for the development of CD4 + Th1 cells. Here, we found that Tyk2 dependency was most striking in CD8 + T cells, in which the production of IFN-+ in response to IL-12/IL-18 was strongly suppressed throughout infection.…”
Section: Tyk2 and T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these mice normally respond to IL-6 and IL-10, suggesting that Tyk2 is dispensable for mediating IL-6 and IL-10 signaling and does not play major roles in IFN-a signaling. We and others have recently shown that the IL-12-induced functions of NK cells and CD4 + T cells are defective in Tyk2 -/-mice [14][15][16][17]. Tyk2 -/-mice showed reduced CD8 + CTL responses following infection with lymphocytic choriomeningitis virus [15].…”
mentioning
confidence: 84%
“…Tyk2-deficient (-/-) mice display a lack of responsiveness to small amounts of IFN-a, but they respond normally to high concentrations of IFN-a [14,15]. Furthermore, these mice normally respond to IL-6 and IL-10, suggesting that Tyk2 is dispensable for mediating IL-6 and IL-10 signaling and does not play major roles in IFN-a signaling.…”
mentioning
confidence: 99%